FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMBERIAN ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS SUMBER HARTA - Pertiwi, Noren Esty; Ahmad Arif; Wahyu Ernawati; Fika Minata (Jurnal Kesehatan dan Pembangunan, 2024)
Breastfeeding as early and exclusively as possible is a major step to improving the survival of the baby. The purpose of this study is known to be the relationship between work, the role of health workers, and premature babies simultaneously with exclusive breastfeeding in the work area of the Sumber Harta Health Center, Musi Rawas Regency in 2023. The study used quantitative design with analytical survey methods and cross sectional approaches. The population in this study was all mothers in the working area of the Sumber Harta Health Center of Musi Rawas Regency who had babies aged more than 6-12 months totaling 192 people, with a sample size of 66 respondents, which was calculated using the minimum sample formula from Slovin. Samples were taken by purposive sampling technique. The data used are primary data collected using questionnaires. Then, the data was analyzed using the Chi Square test. The results of the study found that 44 (66.7%) mothers exclusively breastfed, 34 (66.7%) working mothers, 34 (51.5%) influential health worker roles and 4 (6.1%) premature births. Based on the results of bivariate analysis, it is known that there is a relationship between work (P value = 0.045), the role of health workers (P value = 0.045) and premature babies (P value = 0.010) with exclusive breastfeeding. Occupation, the role of health workers, and premature birth babies have a relationship with exclusive breastfeeding. Keywords— Exclusive breastfeeding, the role of health workers, occupation, and premature birth